Pharmacokinetics, Pharmacodynamics, Safety, and Tolerability of Oral Venglustat in Healthy Volunteers - Peterschmitt, M. Judith; Crawford, Nigel P. S.; Gaemers, Sebastiaan J. M.; Ji, Allena J.; Sharma, Jyoti; Pham, Theresa T. (Clinical pharmacology in drug development, 2021)
Venglustat is a small‐molecule glucosylceramide synthase (GCS) inhibitor designed to reduce the production of glucosylceramide (GL‐1) and thus is expected to substantially reduce formation of glucosylceramide‐based glycosphingolipids. Because of its effect on glycosphingolipid formation, GCS inhibition has therapeutic potential across many disorders affecting glycosphingolipid metabolism. Therefore, venglustat is under development for substrate reduction therapy in multiple diseases, including Gaucher disease type 3, Parkinson's disease associated with GBA mutations, Fabry disease, GM2 gangliosidosis, and autosomal dominant polycystic kidney disease. Phase 1 studies were conducted in healthy volunteers to determine venglustat pharmacokinetics, pharmacodynamics, safety, and tolerability and to assess food effects on pharmacokinetics (single‐dose and food‐effect studies: NCT01674036; repeated‐dose study: NCT01710826). Following a single oral dose of venglustat l‐malate (2, 5, 15, 25, 50, 100, or 150 mg), venglustat demonstrated linear pharmacokinetics, rapid absorption (median tmax, 3.00–5.50 hours), systemic exposure unaffected by food, low apparent total body clearance (mean CL/F, 5.18–6.43 L/h), and pooled geometric mean t1/2z of 28.9 hours. Following repeated once‐daily oral doses of venglustat l‐malate (5, 10, or 20 mg) for 14 days, apparent steady state occurred within 5 days of repeated dosing, with pooled accumulation ratios of 2.10 for Cmax and 2.22 for AUC0–24, and no statistically significant effect of dose or sex on accumulation. The mean fraction of dose excreted unchanged in urine (fe0–24) was 26.3% to 33.1%. Plasma GL‐1 and GM3 decreased time‐ and dose‐dependently. Venglustat demonstrated a favorable safety and tolerability profile.